Endoscopic sphincterotomy - The basics - DS Zimmon (Canadian Journal of Gastroenterology)
Endoscopic sphincterotomy refers to the incision of the terminal portion of the biliary or pancreatic ducts by a variety of techniques, depending on anatomic circumstances, goals and risks. Alternative methods include percutaneous transhepatic or surgical techniques. The initial Erlangen method - complete sphinccerotomy - carried an unavoidable risk of perforation and hemorrhage. Fractional incision or 'endoscopic papillotomy' - incision of the inferior sphincter - carries no risk of hemorrhage or perforation, done properly. Techniques of papillotomy including 'pull,' 'precut,' stent placement, infundibulotomy, percutaneous cholangiography, and internal spring wire are described, and general electrosurgical principles discussed.